Penyuluhan dan Pembinaan Pola Kesehatan Masyarakat Melalui Senam Lansia Di Desa Padang Cermin, Langkat, Sumatera Utara - Mardiana , Mardiana; Br Tarigan, Silviyana; Saputri , Lilis; Sitepu , Dewi Rulia Br; Afni , Khairina; Br Ginting , Cica Ayu Astria; Dinanti, Ivo; Devieta , Alviona (Welfare : Jurnal Pengabdian Masyarakat, 2023)
The community service program aims to: 1.  improve the quality of health among the elderly. 2) To increase the enthusiasm and concern of the elderly for their own health. 3). To help the elderly stay fit and healthy. 4). To increase the awareness of the elderly about how to maintain a healthy diet using a healthy menu in the village of Padang Cermin. The form of community service activities is carried out by making routine gymnastics for the elderly. The subject of service is the elderly community. Implementation of activities through several stages, namely planning and implementation of core activities. The elderly exercise program plays a role in improving the health condition of the elderly, which can be said to be in good health, and there are no complaints of diseases that are too serious; only a few elderly people have complaints of illness.